2014
DOI: 10.4236/pp.2014.53033
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Nitroprusside inhibits HEK293 Cell Growth by cGMP-Dependent and Independent Mechanisms

Abstract: The acute and chronic effects of sodium nitroprusside (SNP) are well characterized for vascular smooth muscle cells (VSMC). Stimulation of soluble guanylyl cyclase (sGC) gives a rapid elevation of intracellular cGMP levels and relaxation of VSMC. The antiproliferative effect of SNP needs days to develop. In the present study human embryonic kidney (HEK 293) cells were used to study the growth after repeated exposure to SNP. A dose-dependent antiproliferative effect was evident and after 5 days with an IC 50 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Consistent with this conclusion, finite elementbased computational modelling has shown that differences in stiffness between the muscle layers and proliferating epithelium are sufficient to drive epithelial folding into the structures observed following smooth muscle differentiation [4,44,45]. This process appears to depend mostly on the static stiffness of the smooth muscle rather than its shortening because reducing gut motility with sodium nitroprusside [46] does not abrogate epithelial folding. Consistently, the computational model generates epithelial folds when the smooth muscle is treated as a stiff, static tissue.…”
Section: Gastrointestinal System (A) Intestinementioning
confidence: 93%
“…Consistent with this conclusion, finite elementbased computational modelling has shown that differences in stiffness between the muscle layers and proliferating epithelium are sufficient to drive epithelial folding into the structures observed following smooth muscle differentiation [4,44,45]. This process appears to depend mostly on the static stiffness of the smooth muscle rather than its shortening because reducing gut motility with sodium nitroprusside [46] does not abrogate epithelial folding. Consistently, the computational model generates epithelial folds when the smooth muscle is treated as a stiff, static tissue.…”
Section: Gastrointestinal System (A) Intestinementioning
confidence: 93%
“…On the other hand, a marked antiproliferative effect was obtained with an apparent IC 50 -value of 250 µM. The antiproliferative potency of cGMP was lower in HEK 293 cells since cGMP concentrations above 1000 µM were needed to reduce cell density 50% [11]. The most important observation in the present study was the reduced sensitivity to cGMP after MRP5 transfection.…”
Section: Discussionmentioning
confidence: 44%
“…Cyclic cGMP was added to the culture medium to elevate intracellular concentrations but the permeability is counteracted by the activity of MRP5 that is an effective efflux pump [8]. In agreement, low extracellular cGMP concentrations (1.0 -10 µM) did not give detectable increase of intracellular concentrations in HEK 293 cells [11] or hRBC [20]. However, these and other studies have shown that cGMP in millimolar concentrations may permeate the membrane from the ectoside.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations